“He Meddled with or Molested Me”: #MeToo protests in Nuala Ní Dhomhnaill’s poetry - Hawk, Chang (Penerbit Universiti Kebangsaan Malaysia, 2021)
The year 2017 was pivotal for women because of the #MeToo movement’s global momentum. People were alerted to the abuses of power and sexual harassment by male authorities in different fields such as government, entertainment and industry. These scandals also helped bring attention to the objectification of women’s normalised bodies and their subjugation in patriarchal cultures. Yet neither this disempowerment of women nor women’s coming forward new, because they have been widely explored in contemporary women’s writing. Examining Nuala Ní Dhomhnaill’s poetry from the prism of #MeToo, this paper discusses women’s imprisonment and silence, their harassment and victimisation and the docility of their bodiesin traditional patriarchal discourse. This paper aims to investigate how women are monitored physically and mentally in male-centred contexts, how they are molested in traditional societies and how they can be empowered by coming forward and telling their own stories.